Distinct requirements for evoked and spontaneous release of neurotransmitter are revealed by mutations in the Drosophila gene neuronal-synaptobrevin. - Deitcher, D.L.; Ueda, A.; Stewart, B.A.; Burgess, R.W.; Kidokoro, Y.; Schwarz, T.L. (Journal of Neuroscience, 1998)
Two modes of vesicular release of transmitter occur at a synapse: spontaneous release in the absence of a stimulus and evoked release that is triggered by Ca2+ influx. These modes often have been presumed to represent the same exocytotic apparatus functioning at different rates in different Ca2+ concentrations. To investigate the mechanism of transmitter release, we have examined the role of synaptobrevin/VAMP, a protein involved in vesicular docking and/or fusion. We generated a series of mutations, including null mutations, in neuronal-synaptobrevin (n-syb), the neuronally expressed synaptobrevin gene in Drosophila. Mutant embryos completely lacking n-syb form morphologically normal neuromuscular junctions. Electrophysiological recordings from the neuromuscular junction of these mutants reveal that the excitatory synaptic current evoked by stimulation of the motor neuron is abolished entirely. However, spontaneous release of quanta from these terminals persists, although its rate is reduced by 75%. Thus, at least a portion of the spontaneous "minis" that are seen at the synapse can be generated by a protein complex that is distinct from that required for an evoked synaptic response.